SCHOOL INSTRUCTIONAL SUPERVISION AND DISPARITIES IN THE ACHIEVEMENT OF EFFECTIVE TEACHING AND LEARNING IN NIGERIAN POST - BASIC SECONDARY SCHOOLS - IDRIS, MUHAMMAD KABIR; JADA, HAMIDU MOHAMMED; GARBA, UMAR (Sokoto Educational Review, 2025)
Effective educational outcomes hinge on robust mechanisms, among which instructional supervision stands as a cornerstone. When properly organized and executed, instructional supervision can significantly enhance the teaching-learning process, ultimately elevating the standards of the educational system. This paper explores the concept of instructional supervision, its various types, their respective impacts, and the disparities in achieving effective teaching and learning in Nigerian post-basic schools. It concludes that consistent, thorough, and ongoing supervision of instruction is critically needed, especially given the recent changes introduced to the secondary school curriculum. DOI: https://doie.org/10.10318/SER.2025840633